PENGARUH PERENDAMAN KEDELAI TERHADAP MUTU SARI KEDELAI - Nazarena, Yunita -; Malahayati, Nura; Priyanto, Gatot (Jurnal Sains dan Teknologi Pangan, 2021)
According to BPOM (2006), soymilk is an emulsion product that is extracted from boiled and ground soybeans with the addition of water. Soymilk is a food product that has several advantages including being cheaper than cow's milk and high nutritional value. The process of making soymilk will affect the quality produced. Soaking soybeans aims to soften the cellular structure of soybeans so that they are easy to grind, provide better dispersion and suspension of soybean solids at the time of extraction and make it easier to peel the soybean skin and result in mold that can ferment soybeans without skin. The research design used was factorial completely randomized design (RALF) with two treatment factors and three replications. The first factor is the immersion temperature (A) consisting of A1 = 30 ° C, A2 = 50 ° C. The second factor is the immersion time (B) consisting of B1 = 9 hours, B2 = 12 hours and B3 = 15 hours. The data obtained were analyzed using the Analysis of Variance (ANOVA) statistical test at a 5% level of confidence using version 9 of the SAS (Statistical Analysis System) program. The treatment that had a significant effect was followed by the Duncan Multiple Range Test (DMRT) difference test. The laboratory examination results showed that the average value of total dissolved solids of soymilk 10.33-15.67% (SNI TPT min 11.50%); the average pH value of soymilk is 6.03-7.02 (SNI pH 6.5-7.0); and soymilk total protein average value 1.07-1.50% (SNI protein min 1.0%). A1B1 treatment (30 ° C, 9 hours) is the best treatment because it meets SNI standards for soybean juice (pH 7.02; TPT 15.67%; protein 1.27%)